2022
DOI: 10.1126/science.abn5679
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging of all-inorganic, interface-stabilized perovskite solar cells

Abstract: To understand degradation routes and improve the stability of perovskite solar cells (PSCs), accelerated aging tests are needed. Here, we use elevated temperatures (up to 110 Celsius) to quantify the accelerated degradation of encapsulated CsPbI 3 PSCs under constant illumination. Incorporating a 2D Cs 2 PbI 2 Cl 2 capping layer between the perovskite active layer and hole-transport layer stabilizes the interface wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 55 publications
1
141
0
Order By: Relevance
“…Their role as a part of the active layer for 2D perovskite, for instance, is not discussed in much detail within the sections. Nevertheless, we would like to provide brief examples and comment on organic cations for 2D perovskite applications, especially considering that the design strategies discussed in this review are highly relevant. For instance, Dou et al recently reported on a Sn­(II)-based 2D perovskite field-effect transistor (FET) with excellent charge carrier mobility facilitated by a linear π-conjugated oligothiophene ligand . These extended conjugated organic molecules serve as robust barriers for oxygen and moisture, while increasing the crystal formation energy through their strong intermolecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Their role as a part of the active layer for 2D perovskite, for instance, is not discussed in much detail within the sections. Nevertheless, we would like to provide brief examples and comment on organic cations for 2D perovskite applications, especially considering that the design strategies discussed in this review are highly relevant. For instance, Dou et al recently reported on a Sn­(II)-based 2D perovskite field-effect transistor (FET) with excellent charge carrier mobility facilitated by a linear π-conjugated oligothiophene ligand . These extended conjugated organic molecules serve as robust barriers for oxygen and moisture, while increasing the crystal formation energy through their strong intermolecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Though the LED source has a limited near-infrared light portion, it can generate values of carrier concentration similar to those of the Xe lamp and, hence, negligibly impacts the performance of solar cells. Therefore, LED sources are widely used in the community for long-term stability tests. , We used an Ossila source meter to record MPP figuresit regularly measures JV , finds V MPP at which maximum power is generated, and keeps the devices at V MPP .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, LED sources are widely used in the community for long-term stability tests. 71,72 We used an Ossila source meter to record MPP figures�it regularly measures JV, finds V MPP at which maximum power is generated, and keeps the devices at V MPP .…”
Section: T H Imentioning
confidence: 99%
“…The new frontier is using a 2D layer of close stoichiometry on top of the 3D structure of the perovskite. It has been shown 87 that devices with this 2D capping layer did not degrade at 35 °C and required >2100 hours at 110 °C under constant illumination for a 20% degradation of their initial efficiency. Degradation acceleration factors based on the observed Arrhenius temperature dependence predict intrinsic lifetimes of 51 000 ± 7000 hours (>5 years) operating continuously at 35 °C.…”
Section: Sustainability By Fully Inorganic Perovskitesmentioning
confidence: 99%
“…An important update has been just published in Science 87 on the long-term durability of CsPbI 3 -based devices. The new frontier is using a 2D layer of close stoichiometry on top of the 3D structure of the perovskite.…”
Section: Sustainability By Fully Inorganic Perovskitesmentioning
confidence: 99%